Acquisition and Development of Verb/Predicate Chaining in Hebrew - Berman, Ruth; Lustigman, Lyle (Frontiers in Psychology, 2020)
The study considers development and use of verb/predicate chaining constructions by Hebrew speakers from early childhood to adolescence, based on analysis of authentic conversational and narrative corpora. Three types of constructions are analyzed, ordered hierarchically by degree of cohesivity and obligatoriness of chaining: (1) monoclausal complex predicates (the “extended predicates” of traditional Hebrew grammars); (2) coreferential interclausal predicate chaining; and (3) discursively motivated topic chaining. Relevant typological features of Modern Hebrew are reviewed as accounting for the absence of canonical clause chaining in the language (the paucity of non-finite constructions in everyday usage, absence of an uninflected basic form of verbs, lack of auxiliary verbs, and monolexemic verb-internal complexity). Monoclausal verb chaining emerges early in the speech of toddlers in interaction with their caretakers, whereas predicate chaining by coordination across clauses occurs only later, and chunking of such constructions at the service of discourse connectivity is found only from school-age. Non-finite subordination emerges as an advanced form of clause combining, in contrast to straightforward subordination with the multifunctional subordinator še ‘that’. Two main conclusions follow from the study: First, the innovative hierarchy defined here for different degrees of verb/predicate linkage mirrors developmental phases in child language; and, second, monoclausal chains of finite verbs or verbal operators followed by infinitival complements are grammatically obligatory, and are common from an early age, whereas bi- and multi-clausal predicate chaining represents an optional rhetorical choice on the part of a given speaker–writer in a particular communicative context.